2014
DOI: 10.1111/petr.12232
|View full text |Cite
|
Sign up to set email alerts
|

Stable pediatric kidney transplant recipients run higher urine indoleamine 2, 3 dioxygenase (IDO) levels than healthy children

Abstract: Immune cells utilize the indoleamine 2,3 dioxygenase (IDO) enzymatic conversion of tryptophan (trp) to kynurenines (kyn) to determine T cell activation versus anergy/apoptosis. In prior studies, urine IDO levels were higher in rejecting renal allografts than in stable state. However, urine IDO levels in healthy subjects or children are unknown. As a corollary to a larger longitudinal and prospective study of serum and urine IDO levels for transplant immune monitoring, here we analyzed the difference between ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…We found viremia in almost three‐quarters of our patients. The incidences of EBV, CMV, and BKV were consistent with those in other reported pediatric series, as well as in one adult series . Previous large studies and surveys of posttransplantation viral infection in pediatric kidney transplantation have examined only EBV, CMV, and BKV.…”
Section: Discussionsupporting
confidence: 88%
“…We found viremia in almost three‐quarters of our patients. The incidences of EBV, CMV, and BKV were consistent with those in other reported pediatric series, as well as in one adult series . Previous large studies and surveys of posttransplantation viral infection in pediatric kidney transplantation have examined only EBV, CMV, and BKV.…”
Section: Discussionsupporting
confidence: 88%
“…It has been defined as the tryptophan utilisation theory [ 18 ]. The IDO pathway and tryptophan draining lead to direct immune cell inactivation and can deploy regulatory factors [ 34 ]. Moreover, tryptophan metabolites, namely, kynurenine, quinolinic and picolinic acids, can directly affect CD8 and CD4 T-helper cells [ 35 ].…”
Section: Immunosuppressive Mechanisms Of Ido1mentioning
confidence: 99%
“…Interestingly, another group showed that stable pediatric kidney Tx recipients (no acute graft rejection and no infection) had significantly higher urine kynurenine/tryptophan ratios within the first month post-Tx compared to healthy children. This suggests that a slightly increased tryptophan catabolism may probably reflect the maintenance of the stable immunological/anti-inflammatory state after Tx [ 142 ]. Holmes et al were the first to report that serum kynurenine levels significantly increase at five–seven days before biopsy-proved kidney allograft rejections, as well as in cases of viral or bacterial infections [ 143 ].…”
Section: Diagnostic and Prognostic Role Of Tryptophan And Its Metamentioning
confidence: 99%